2022
DOI: 10.48550/arxiv.2206.02460
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Probing spin dynamics of ultra-thin van der Waals magnets via photon-magnon coupling

Abstract: Layered van der Waals (vdW) magnets can maintain a magnetic order even down to the single-layer regime 2,3,9 and hold promise for integrated spintronic devices 4,5 . While the magnetic ground state of vdW magnets was extensively studied, key parameters of spin dynamics, like the Gilbert damping, crucial for designing ultra-fast spintronic devices, remains largely unexplored. Despite recent studies covering the optical frequency range 6,7 , achieving spin wave control at microwave frequencies is highly desirabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 37 publications
(51 reference statements)
0
5
0
Order By: Relevance
“…This essentially means that when we aim to probe spin dynamics of 2D vdW monolayers (which are typically µm sized flakes) using microwave photons, the photon mode must have a correspondingly small mode size to maximize the coupling strength and hence its sensitivity. One of the promising approaches to this is to use on-chip superconducting (SC) resonators [176,186,187]. Strong coupling between photons in SC resonators and magnons in anti-ferromagnetic CrCl 3 bulk systems has been demonstrated [186,187].…”
Section: Magnon-photon Coupling Probed In a Superconducting Resonatormentioning
confidence: 99%
See 4 more Smart Citations
“…This essentially means that when we aim to probe spin dynamics of 2D vdW monolayers (which are typically µm sized flakes) using microwave photons, the photon mode must have a correspondingly small mode size to maximize the coupling strength and hence its sensitivity. One of the promising approaches to this is to use on-chip superconducting (SC) resonators [176,186,187]. Strong coupling between photons in SC resonators and magnons in anti-ferromagnetic CrCl 3 bulk systems has been demonstrated [186,187].…”
Section: Magnon-photon Coupling Probed In a Superconducting Resonatormentioning
confidence: 99%
“…Strong coupling between photons in SC resonators and magnons in anti-ferromagnetic CrCl 3 bulk systems has been demonstrated [186,187]. Zollitsch et al recently reported that it is possible to probe spin dynamics of Cr 2 Ge 2 Te 6 as thin as 11 nm using SC resonators [176]. Cr 2 Ge 2 Te 6 flakes were exfoliated and transferred onto magnetically-active parts of high-qualityfactor SC lumped element resonators with their small mode volume (≈ 6000 µm 3 ), as schematically shown in Fig.…”
Section: Magnon-photon Coupling Probed In a Superconducting Resonatormentioning
confidence: 99%
See 3 more Smart Citations